KONFLIK BATIN TOKOH DALAM NOVEL MEMANG JODOH KARYA MARAH RUSLI - Rinda Valentari; Abdul Jalil; Hadi Rumadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRAK: This study discusses the inner conflicts of figure in novel Memang Jodoh opus Marah Rusli. Discuss the inner conflict which occurs of each figure in novel Memang Jodoh opus Marah Rusli. In addition, this study also discusses from external factor and internal factor to evoked the inner conflicts of figure in novel Memang Jodoh opus Marah Rusli. This study used a qualitative approach and descriptive method that aims to describe inner conflicts of figure in novel Memang Jodoh opus Marah Rusli to evoked by external factor and internal factor. The results of the research is a classification of inner conflicts of figure found in novel Memang Jodoh opus Marah Rusli. The results of this study also as a form of documentation inner conflicts of figure in novel Memang Jodoh opus Marah Rusli.Keywords: Inner confllicts, figure, the novel Memang Jodoh opus Marah Rusli.